Pengaruh Kepemimpinan Islami, Etos Kerja Islami, dan Motivasi Kerja Islami Terhadap Kinerja Karyawan Dengan Organizational Citizenship Behavior Sebagai Variabel Intervening pada PT. Asuransi Askrida Syariah - Adi Rosyadi; Soeharjoto Soeharjoto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Indonesia's Islamic insurance industry has expanded rapidly, requiring human resource management that goes beyond financial targets to embed Islamic values into all operational aspects. This study examines the impact of Islamic leadership, Islamic work ethic, and Islamic work motivation on employee performance, with Organizational Citizenship Behavior (OCB) as a mediating variable at PT. Asuransi Askrida Syariah. A quantitative approach with a causal-associative design was adopted. Data were gathered from 200 permanent employees through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). Hypothesis testing confirms that all three independent variables positively and significantly influence OCB, with Islamic work motivation emerging as the strongest predictor. OCB consistently and significantly enhances employee performance. In direct paths, Islamic work ethic and Islamic work motivation positively affect performance, whereas Islamic leadership exhibits a negative direct effect. Nonetheless, Islamic leadership effectively boosts performance via an indirect pathway through OCB. These findings reinforce the notion that internalizing Islamic values is more effective in elevating performance through fostering positive organizational behavior, contributing empirical evidence to the development of Sharia-based human resource management.